Combinatorial DNA methylation codes at repetitive elements - Papin, Christophe; Ibrahim, Abdulkhaleg; Gras, Stéphanie Le; Velt, Amandine; Stoll, Isabelle; Jost, Bernard; Menoni, Hervé; Bronner, Christian; Dimitrov, Stefan; Hamiche, Ali (Genome Research, 2017)
DNA methylation is an essential epigenetic modification, present in both unique DNA sequences and repetitive elements, but its exact function in repetitive elements remains obscure. Here, we describe the genome-wide comparative analysis of the 5mC, 5hmC, 5fC, and 5caC profiles of repetitive elements in mouse embryonic fibroblasts and mouse embryonic stem cells. We provide evidence for distinct and highly specific DNA methylation/oxidation patterns of the repetitive elements in both cell types, which mainly affect CA repeats and evolutionarily conserved mouse-specific transposable elements including IAP-LTRs, SINEs B1m/B2m, and L1Md-LINEs. DNA methylation controls the expression of these retroelements, which are clustered at specific locations in the mouse genome. We show that TDG is implicated in the regulation of their unique DNA methylation/oxidation signatures and their dynamics. Our data suggest the existence of a novel epigenetic code for the most recently acquired evolutionarily conserved repeats that could play a major role in cell differentiation.